2020
DOI: 10.1111/hae.14127
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mass and hypovitaminosis D in haemophilia: A single‐centre study in patients with severe and moderate haemophilia A and B

Abstract: Introduction: Haemophilia (H) is frequently associated with a multifactorial reduction in bone mineral density (BDM), but little is known about possible differences between HA and HB according to their severity. Aim: To evaluate the association between low bone mineral density (BMD), 25-hydroxyvitamin D [25(OH)D] concentrations and bone turnover markers in patients with HA and HB younger or older than 50 years. Methods: In 78 patients <50 years and 33 patients >50 years with severe (S) or moderate (M) HA and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Analysing the available medical documentation of patients, the authors also noted the prevalence of vitamin D deficiency in patients with haemophilia A and B—sufficient vitamin D levels were noted in 1/5 of patients, which is in accordance with the results of other studies [ 15 , 19 , 31 ]. According to researchers, vitamin D deficiency may be dictated by geographical location and not only by disease entity—most studies report that vitamin D deficiency is common in the European population [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Analysing the available medical documentation of patients, the authors also noted the prevalence of vitamin D deficiency in patients with haemophilia A and B—sufficient vitamin D levels were noted in 1/5 of patients, which is in accordance with the results of other studies [ 15 , 19 , 31 ]. According to researchers, vitamin D deficiency may be dictated by geographical location and not only by disease entity—most studies report that vitamin D deficiency is common in the European population [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…Due to reports in the literature on the frequent occurrence of low bone mass in both adults and children with congenital haemophilia [ 15 , 19 , 31 , 32 , 33 ], the authors analysed the concentrations of selected markers of bone turnover in the venous blood of adult patients with haemophilia A and B. They demonstrated a statistically significant difference in osteocalcin values compared to a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific effect of FVIII on BMD has been suggested by in vitro studies and the differences between HA and HB observed in Italian PWHs. 16,37 In our population, the comparison of HA and HB patients did not show clear differences, which is in line with an animal study 12 and a study on 14 HB patients in Iran, 38 which showed that HB also may lead to low BMD, not different from HA.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, they delineated significantly reduced BMD of the femoral neck and an insignificant reduction in total hip BMD (25). Several more recent case-control studies also reported reduced BMD at these two skeletal sites, but did not find any significant differences in the lumbar spine (23,(26)(27)(28)(29)(30)(31).…”
Section: Low Bone Mineral Density In Hemophiliacsmentioning
confidence: 97%